Effects of vibration on removal of solid particles from waste water - Jong, Shin Poh (Universiti Malaysia Sarawak, UNIMAS, 2010)
In conjunction with rapid development of the country, pollution issues are also getting serious. Besides the environmental legislative enforcement laws and establishment of organizations and societies fighting for application of environmental friendly steps in all sort of human activities, there are also invention of various methods and technologies to mitigate the effects of pollution. A circular phase separator embedded with coalescing medium in co-current flow was developed a few years ago for treating wastewaters loaded with oil droplets and suspended solids. The arrangement consists of four series of inclined frustums with each of the series consist of several successive layers of frustums. The series of frustums are placed in an up-right and inverted positions that subsequently form a multiple-angle arrangement. This arrangement helps promote faster rising of oil droplets through coalescence process, and rapid settling of solid particles. The inlet of the separator is equipped with an up-flow center-feed perforated-pipe distributor to direct flow to the series of parallel inclined coalescing plates in a co-current flow. In this research, the x vibration will be applied to the separator to know how the vibration influences the removal of TSS from the water. The removal efficiency of MFCoC separator was previously researched to attain 49.54%. In this research, vibration was applied in an attempt to enhance its performance; however, the removal efficiency recorded 47.68% (approximately 1.86% lower than “without vibration”). The comparison was also made between the MFCoC separator and DPCC separator. For DPCC separator, the efficiency of TSS removal was approximately 30.12% in current research (with vibration) and 56.34% for the previous research (without the application of vibration). From the above results, it was shown that there was the decrease in TSS removal efficiency after the application of vibration to both MFCoC and DPCC separators. Therefore, it can be concluded that vibration (at current amplitude produced by angle grinder) did not enhance the removal of solid particles from water.